Future danger posed by fungi in the Ophiostomatales when encountering new hosts. (August 2016) - Musvuugwa, Tendai; Dreyer, Léanne L.; Roets, Francois
Abstract: The Ophiostomatales contain pathogens that threaten forests world-wide. Global trade increases encounters with new hosts, with potential devastating consequences. We assessed the danger posed by the movement of Ophiostomatales between different host trees in South Africa. We tested the pathogenicity of five fungal species from native South African trees, and three from exotic trees, on various native and exotic trees. To evaluate the potential of fungi to move to new hosts, we investigated the strength of their associations with arthropod vectors. Results indicate that many fungal species are pathogens of newly encountered and distantly-related hosts. Encounters of pathogens with new hosts are less likely when host plants are distantly related, and outside the host range of boring beetle vectors, which also reduces the chances of vectoring by phoretic mite associates. However, pathogens associated with numerous mite species and wounds are more likely to encounter new hosts and pose future threats.